Disseminated Multifocal Intracerebral Bleeding Events in Three Coronavirus Disease 2019 Patients on Extracorporeal Membrane Oxygenation As Rescue Therapy. - Bihlmaier, Karl; Coras, Roland; Willam, Carsten; Grampp, Steffen; Jabari, Samir; Eichhorn, Philip; Haller, Florian; Kuramatsu, Joji; Schwab, Stefan; Castellanos, Ixchel; Birkholz, Torsten; Schüttler, Jürgen; et al. (Critical Care Explorations, 2020)
Objectives: To describe three coronavirus disease 2019 patients suffering from acute respiratory distress syndrome under venovenous extracorporeal membrane oxygenation therapy and tight anticoagulation monitoring presenting a novel pattern of multifocal brain hemorrhage in various degrees in all cerebral and cerebellar lobes. Design: Clinical observation of three patients. Post mortem examinations. Setting: Two ICUs at the University Hospital Erlangen. Patients: Three patients (medium age 56.6 yr, two male with hypertension and diabetes, one female with no medical history) developed severe acute respiratory distress syndrome on the basis of a severe acute respiratory syndrome coronavirus 2 infection. All required mechanical ventilation and venovenous extracorporeal membrane oxygenation support. Interventions: Clinical observation, CT, data extraction from electronic medical records, and post mortem examinations. Main Results: We report on an unusual multifocal bleeding pattern in the white matter in three cases with severe acute respiratory distress syndrome due to coronavirus disease 2019 undergoing venovenous extracorporeal membrane oxygenation therapy. Bleeding pattern with consecutive herniation was found in CT scans as well as in neuropathologic post mortem examinations. Frequency for this unusual brain hemorrhage in coronavirus disease 2019 patients with extracorporeal membrane oxygenation therapy at our hospital is currently 50%, whereas bleeding events in extracorporeal membrane oxygenation patients generally occur at 10-15%. Conclusions: Multifocality and high frequency of the unusual white matter hemorrhage pattern suggest a coherence to coronavirus disease 2019. Neuropathological analyses showed circumscribed thrombotic cerebrovascular occlusions, which eventually led to microvascular and later on macrovascular disseminated bleeding events. However, signs of cerebrovascular inflammation could not be detected. Polymerase chain reaction analyses of brain tissue or cerebrospinal fluid remained negative. Increased susceptibility for fatal bleeding events should be taken into consideration in terms of systemic anticoagulation strategies in coronavirus disease 2019.
EVALuna2:313697
Keywords: acute respiratory distress syndrome; cerebral microhemorrhage; coronavirus disease 2019; extracorporeal membrane oxygenation; intracerebral bleeding

Endogenous De Novo Synthesis of Isopropanol Following Severe Non-Diabetic Ketoacidosis in a Patient With Duchenne Muscular Dystrophy - Bihlmaier, Karl; Grampp, Steffen; Willam, Carsten; Schiffer, Mario; Herbst, Larissa (Journal of Endocrinology and Metabolism, 2022)
In Duchenne muscular dystrophy (DMD), patients seem prone to severe metabolic acidosis following excessive bicarbonate loss due to laxative use or gastrointestinal disorders. In addition, hypoalimentation and fasting can cause life-threatening non-diabetic ketoacidoses with acetonemia in these patients. Isopropanolemia instead is predominantly found following intoxication. Only few reports exist describing isopropanolemia in diabetic or alcoholic ketoacidosis. Here, we report on a patient suffering from DMD who developed lifethreatening non-diabetic ketoacidosis, acetonemia, and endogenous de novo synthesis of isopropanol following glucose fasting. We hypothesize isopropanolemia being a byproduct of acetone metabolism, possibly in association with a metabolic predisposition in patients with DMD such as an altered NADH/NAD(+) ratio leading to a reduction from acetone to isopropyl alcohol whilst in severe ketoacidosis.
CRIS-Team WoS Importer:2022-07-01
Keywords: Isopropanolemia; Acetonemia; Ketoacidosis; Refeeding syndrome; Duchenne muscular dystrophy

Fatal Puumala Hantavirus Infection in a Patient with Common Variable Immunodeficiency (CVID) - Steininger, Philipp; Herbst, Larissa; Bihlmaier, Karl; Willam, Carsten; Koerper, Sixten; Schrezenmeier, Hubert; Klueter, Harald; Pfister, Frederick; Amann, Kerstin Ute; Weiss, Sabrina; Krueger, Detlev H.; Zimmermann, Robert; et al. (Microorganisms, 2023)
Puumala hantavirus (PUUV) infections usually show a mild or moderate clinical course, but may sometimes also lead to life-threatening disease. Here, we report on a 60-year-old female patient with common variable immunodeficiency (CVID) who developed a fatal PUUV infection with persistent renal failure, thrombocytopenia, and CNS infection with impaired consciousness and tetraparesis. Hantavirus-specific antibodies could not be detected due to the humoral immunodeficiency. Diagnosis and virological monitoring were based on the quantitative detection of PUUV RNA in blood, cerebrospinal fluid, bronchial lavage, and urine, where viral RNA was found over an unusually extended period of one month. Due to clinical deterioration and virus persistence, treatment with ribavirin was initiated. Additionally, fresh frozen plasma (FFP) from convalescent donors with a history of PUUV infection was administered. Despite viral clearance, the clinical condition of the patient did not improve and the patient died on day 81 of hospitalization. This case underlines the importance of the humoral immune response for the course of PUUV disease and illustrates the need for PCR-based virus diagnostics in those patients. Due to its potential antiviral activity, convalescent plasma should be considered in the therapy of severe hantavirus diseases.
CRIS-Team Scopus Importer:2023-03-10
Keywords: common variable immunodeficiency; convalescent plasma; encephalitis; Puumala hantavirus; ribavirin

β-(1→3)-D-glucan- and mannan-guided early termination of antifungal therapy in ICU patients: a randomized controlled study - Erb, Timothy; Mihai, Sidonia; Strauss, Richard; Herbst, Larissa; Castellanos, Ixchel; Diesch, Katharina; Cipa, Franziska; Bihlmaier, Karl; Lang, Anne-Katharina; Ganslmayer, Marion; Willam, Carsten; Bremer, Frank Felix; et al. (Antimicrobial Agents and Chemotherapy, 2023)
Candida spp. are frequently encountered in specimens from ICUs. However, most of these detections represent colonization. Nevertheless, clinical practice shows that a considerable proportion of these patients will receive antifungal therapy (AT). β-(1→3)-D-glucan (BDG) and mannan are fungal biomarkers with high negative predictive values. We aimed to examine whether biomarker-guided discontinuation of AT can reduce the antifungal consumption. Therefore, we conducted a prospective, randomized intervention study between 1 April 2019 and 31 March 2020. All adult ICU patients with a newly started systemic AT but without fungal infection were eligible for inclusion. Enrolled patients were randomized into an intervention and a control group. In both groups, serum BDG and mannan were determined on days 1 and 2 of AT. If all measurements were negative, AT was discontinued in the intervention group. The primary endpoint was antifungal use. The study was terminated after 12 months. Until this time-point, 41 patients had been included. In the intervention group (n = 19), AT was stopped in only two patients because all others showed either positive BDG and∕or mannan levels. One of these two patients developed candidemia and AT had to be restarted. There was no significant difference in the primary and secondary endpoints. In summary, the strategy of using two negative BDG and mannan levels to stop AT failed to reduce antifungal consumption in our cohort. Indeed, there will inevitably be patients with invasive candidiasis in whom necessary AT is discontinued. The optimal patient population, biomarker set, and termination criteria are critical to the success of biomarker-based termination strategies.
CRIS-Team Scopus Importer:2023-12-15
Keywords: antibiotic stewardship; antifungal therapy; biomarker; Candida infection; candidemia; candidosis; discontinuation; fungal infection